2016
DOI: 10.1007/s00198-016-3759-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term step aerobics exercise on bone metabolism and functional fitness in postmenopausal women with low bone mass

Abstract: The current short-term GBSA exercise benefited to bone metabolism and general health by significantly reduced bone resorption activity and improved functional fitness in PMW with low bone mass. This suggested GBSA could be adopted as a form of group-based exercise for senior community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 40 publications
3
36
0
1
Order By: Relevance
“…The authors emphasized that the results were affected by a large individual variability. In another study [33] of 48 postmenopausal women with low BMD there were no differences in the concentrations of CTX and OC between the group of patients after a 10-week groupbased step aerobics and the control group. The different results were obtained by Mohr et al [34], who analyzed influence of 15 weeks of different forms of training on female population.…”
Section: Prace Oryginalnementioning
confidence: 87%
“…The authors emphasized that the results were affected by a large individual variability. In another study [33] of 48 postmenopausal women with low BMD there were no differences in the concentrations of CTX and OC between the group of patients after a 10-week groupbased step aerobics and the control group. The different results were obtained by Mohr et al [34], who analyzed influence of 15 weeks of different forms of training on female population.…”
Section: Prace Oryginalnementioning
confidence: 87%
“…Unlike osteocalcin, the change in CTX-1 after training was unclear. Studies by Alp 2 on premenopausal women and by Wen et al 49 on postmenopausal women showed that CTX-1 decreased after 2 months of training with moderate intensity in 60-85% of maximal heart rate, 40 min per session, five times per week and 75-85% of heart rate reserve, 90 min per session, three times per week, respectively. A study by Adami et al found that CTX-1 was unchanged after 1 month of training (90 min/session, 3-4 times/week).…”
Section: Discussionmentioning
confidence: 94%
“…This observation could be attributed to the low compliance to calcium supplements intake of our population. Makras Moreover, even short-term aerobic exercise can improve functional fitness and reduce bone resorption in women with low bone mass 27 . In this study, the percentage of women who underwent regular aerobic exercise was relatively low (19.2% vs 15.8%, for women under treatment with denosumab and bisphosphonates, respectively).…”
Section: Discussionmentioning
confidence: 99%